3

This:

\documentclass{article}

\usepackage{amsmath}

\begin{document}

\begin{align*}
    s_yp&=s_zp                  &&  \Longleftrightarrow\\
    S_yp &= S_zp                    &&  \Longleftrightarrow\\
    S_y\left(\sum_{x}a_x\delta_x\right) &=S_z\left(\sum_{x}a_x\delta_x\right)   &&  \overset{Z\text{-Linearität}}{\Longleftrightarrow}\\
    \sum_{x}a_x\left(S_y\delta_x\right)&=
    \sum_{x}a_x\left(S_z\delta_x\right)&&   \Longleftrightarrow\\
    \sum_{x}a_x\left(S_z\delta_x\right.&-\left.S_y\delta_x\right)=0 &&  \Longleftrightarrow\\
    \sum_{x}a_x\left(S_z\right.&-\left.S_y\right)\delta_x = 0
\end{align*}

\end{document}

Produces that:

enter image description here

How can I make the arrows line up ignoring the overset?

Thank you in advance.

2 Answers 2

2

I apply a \mathclap to the text (mathtools required).

\documentclass{article}

\usepackage{amsmath,mathtools}

\begin{document}

\begin{align*}
    s_yp&=s_zp                  &&  \Longleftrightarrow\\
    S_yp &= S_zp                    &&  \Longleftrightarrow\\
    S_y\left(\sum_{x}a_x\delta_x\right) &=S_z\left(\sum_{x}a_x\delta_x\right)   &&  \overset{\mathclap{Z\text{-Linearität}}}{\Longleftrightarrow}\\
    \sum_{x}a_x\left(S_y\delta_x\right)&=
    \sum_{x}a_x\left(S_z\delta_x\right)&&   \Longleftrightarrow\\
    \sum_{x}a_x\left(S_z\delta_x\right.&-\left.S_y\delta_x\right)=0 &&  \Longleftrightarrow\\
    \sum_{x}a_x\left(S_z\right.&-\left.S_y\right)\delta_x = 0
\end{align*}

\end{document}

enter image description here

1

In addition to using a directive such as \makebox[0pt][c]{...} to contain the first argument of \overset (or, use \mathclap), you should (a) get rid of all \left and \right parenthesis-sizing directives -- use \biggl( and \biggr) for the four large parentheses in the third row -- and (b) align all equations on their respective = symbols.

enter image description here

\documentclass{article}
\usepackage[T1]{fontenc}
\usepackage[utf8]{inputenc}
\usepackage{amsmath} % for 'align*' environment
\begin{document}

\begin{align*}
s_yp &= s_zp       &&  \Longleftrightarrow\\
S_yp &= S_zp       &&  \Longleftrightarrow\\
S_y\biggl(\sum_{x}a_x\delta_x\biggr)  
     &=S_z\biggl(\sum_{x}a_x\delta_x\biggr)   
     &&  \overset{\text{\makebox[0pt][c]{$Z$-Linearität}}}{\Longleftrightarrow}\\
\sum_{x}a_x(S_y\delta_x) 
     &= \sum_{x}a_x(S_z\delta_x)
     &&   \Longleftrightarrow\\
\sum_{x}a_x(S_z\delta_x - S_y\delta_x) &= 0 
     &&  \Longleftrightarrow\\
\sum_{x}a_x(S_z- S_y)\delta_x          &= 0
\end{align*}

\end{document}

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .